2004
DOI: 10.1242/jeb.00866
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and significance of reduced activity and responsiveness in resting frog tadpoles

Abstract: where a weight attached to the mucus simulates the force as it hangs. Simulated attachment reduces responsiveness and spontaneous fictive swimming activity. We have recorded the activity and responses of trigeminal neurons innervating the cement gland. They are spontaneously active and simulating attachment results in a sustained increase in this activity. We propose that hanging from a mucus strand increases firing in cement gland afferents. This leads to tonic GABA inhibition that reduces tadpole activity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 52 publications
4
21
0
Order By: Relevance
“…Related to this issue, a recent study has investigated the potential involvement of NO in the mid-hindbrain reticulospinalmediated stopping response in Xenopus embryos (Lambert et al, 2004). At this early stage in development, they failed to find a prominent role for NO in this pathway using NO synthase inhibitors, which is consistent with the notion that an endogenous role for NO in mediating GABA release does not appear reliably until larval stages.…”
Section: Modulation Of Descending Systems By Nitric Oxidementioning
confidence: 69%
“…Related to this issue, a recent study has investigated the potential involvement of NO in the mid-hindbrain reticulospinalmediated stopping response in Xenopus embryos (Lambert et al, 2004). At this early stage in development, they failed to find a prominent role for NO in this pathway using NO synthase inhibitors, which is consistent with the notion that an endogenous role for NO in mediating GABA release does not appear reliably until larval stages.…”
Section: Modulation Of Descending Systems By Nitric Oxidementioning
confidence: 69%
“…The methods for making recordings from the motor nerves have been described previously (e.g. Lambert et al, 2004). Briefly, tadpoles were anaesthetised with 0.1% MS-222 in saline for 20-30 s, then pinned onto a rotatable Sylgard block in a bath of saline.…”
Section: Electrophysiologymentioning
confidence: 99%
“…Each tadpole was tested once. We checked that they were not attached to the bottom of the dish by cement from their cement gland since this inhibits responses (Lambert et al, 2004). We first evaluated spontaneous swimming in unstimulated tadpoles.…”
Section: Basic Swimming Responses To Water Currentsmentioning
confidence: 99%
“…This unique behavior depends on the mandibular branch of trigeminal sensory nerve that senses the attachment state of the embryos and suppresses muscle movement (Lambert et al 2004). A recent study showed that brain-derived neurotrophic factor secreted from the cement gland could provide a short-range attractive guidance signal that stimulates axon arborization and growth into the cement gland (Huang et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…They form an ophthalmic and a mandibular branch, and the latter has a transient pathway that innervates the embryonic cement gland (Roberts and Clarke 1982;Jacobson and Huang 1985). This branch has been shown to regulate attachmentdependent suppression of the embryo's swimming behavior (Lambert et al 2004).…”
Section: Introductionmentioning
confidence: 99%